Preventable causes of death and factors associated with newborn survival at a university hospital in Curitiba, Paraná, Brazil - Simões,Mona A. (2016)
ABSTRACT Introduction: The analysis of deaths occurred in the neonatal period and the association of these data to necropsy data are crucial to reduce infant mortality rate worldwide. Objective: To analyze the preventable causes of death and the factors associated with a higher risk of early newborn death. Methods: A cross-sectional and descriptive study was performed with data about newborns that died during the neonatal period at a university hospital located in Curitiba; 314 cases of pediatric necropsies were selected, and preventable causes of death, survival time, sex, weight, gestational age, first- and fifth-minute Apgar score, cyanosis, acidosis, meconium aspiration, the need for oxygen resuscitation, cause of death and baseline disease were analyzed. Results: When considering only the cause of death, 300 cases (95.54%) would have preventable causes, but when analyzing the underlying disease, the number of cases decreased to 209 (66.56%). The most frequent cause of death was hypoxia (85%), and the main baseline disease was diffuse alveolar damage (52.9%). There was a positive association between these variables with survival time: cyanosis (p = 0.02), gestational age (p = 0.012), cause of death (p < 0.001), Apgar score < 6 (p < 0.001) and pH value (p < 0.001). Conclusion: The incidence of preventable causes of death is probably lower when analyzed concurrently with the underlying disease. Cyanosis, gestational age, cause of death, Apgar < 6 and arterial blood pH are associated with survival time of newborns.